Association of lower urinary tract symptoms and geriatric nutritional risk index in men: a cross-sectional study based on NHANES - Zheng, Tianyun; Sun, Huaibin; Tang, Yueqing; Zeng, Yuan; Yan, Lei (Frontiers in Medicine, 2024)
Background: Despite previous literature exploring the factors influencing lower urinary tract symptoms (LUTS), few studies have examined the relationship between nutritional status and LUTS.The objective of this research was to evaluate the relationship between LUTS and Geriatric Nutritional Risk Index (GNRI) in middle-aged and older men.We included 2607 men in the NHANES 2005-2006 and 2007-2008 cycles for cross-sectional analysis. We screened for LUTS based on four specific questions on the relevant questionnaire. We calculated GNRI according to the relevant calculation formula and included other covariates.Multivariate logistic analysis using GNRI as the principal independent variable and adjusting for other covariates were used to determine the association with LUTS, nocturia, and daytime LUTS.Results: According to the responses to the questionnaire, out of 2607 eligible participants, 471 had LUTS, 906 had nocturia, and 819 had daytime LUTS. In the unadjusted regression model, LUTS (OR = 0.93, 95% CI = 0.91-0.96, P < 0.001), nocturia (OR = 0.90, 95% CI = 0.88-0.93, P < 0.001), and daytime LUTS (OR = 0.96, 95% CI = 0.94-0.99, P = 0.002) were significantly negatively associated with GNRI. After adjustment by adding covariates, LUTS (OR =0.97,95% CI =0.94-0.99, P = 0.026) and nocturia (OR=0.94, 95% CI =0.91-0.93, P <0.001) were significantly negatively associated with GNRI.Conclusions: Low GNRI was associated with the development of LUTS. In the prevention and treatment of LUTS, urologists should consider the impact of nutritional status on LUTS, and interventions for nutritional status may prevent and improve LUTS.